Stress-activated pyrolytic carbon nanofibers for electrochemical platforms. (10th November 2018) - Holmberg, Sunshine; Ghazinejad, Maziar; Cho, EunByul; George, Derosh; Pollack, Brandon; Perebikovsky, Alexandra; Ragan, Regina; Madou, Marc
Abstract: Carbon's electrochemistry depends on its type and microstructure, and how these affect the electrode's electronic density of states. We demonstrate how pyrolysis of electro-mechanically stressed Polyacrylonitrile (PAN) nanofibers, infused with carbon nanotubes, will result in a unique graphitic electrode, which possesses enhanced and multifaceted electrochemical behavior. As corroborated by materials characterization, the microstructure of the stress-activated pyrolytic carbon (SAPC) characteristically contains a high proportion of disorders in the forms of edge planes and embedded heterogeneous nitrogen atoms. These disorders introduce a range of energy states near the Fermi level, yielding enhanced kinetics in the as-synthesized SAPC electrodes. A comprehensive electrochemical study of the SAPC electrode in surface sensitive ([Fe(CN)6 ] 3-/4- ), surface insensitive ([IrCl6 ] 2-/3- ), and adsorption sensitive (dopamine) redox probes demonstrates 5–14-fold increases in its heterogeneous electron transfer rate compared to regular PAN-based carbon electrodes. The fast kinetics of SAPC electrodes in adsorption sensitive analytes translates into its capability for simultaneous detection of dopamine, uric acid, and ascorbic acid. The results point to a new class of pyrolytic carbon electrodes with an attractive electrocatalytic capacity, geared toward electrochemical sensing platforms. Highlights: Pyrolysis of stress-treated polymer nanofibers results in graphitized carbon. Microstructure of pyrolyzed carbon is rich in edge planes and nitrogen heteroatoms. Disorder-induced electroactive sites enhance carbon probes electrochemical kinetics. Stress-activated carbon can simultaneously detect dopamine, uric and ascorbic acids. Electrocatalytic activity of stress-activated carbon holds promise for sensing.